FINDING THE SOLUTION OF FIRST-ORDER LINEAR ORDINARY DIFFERENTIAL EQUATIONS IN THE MAPLE SOFTWARE IN THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2023)
XXI century is the century of technologies. Therefore, the proper use of various modern information media during the educational process, the organization, management, and control of lessons in the process of computer education according to the relationship between the student and the computer are among the urgent issues today. Natural sciences and technology Many problems encountered in the sciences are reduced to differential equations, that is, finding their analytical solution is an extremely difficult problem, therefore, the use of approximate solution methods is more effective. To solve such problems, there are mathematical packages, and this article talks about solving differential equations in the Maple program. That is, the program for finding the analytical solution of the first-order linear ordinary differential equation in the Maple program was created and the result was obtained.